TRANSGENERATIONAL MODELS OF MARRIAGE: EXPERIENCE WITH GENOGRAMS - Терещенко, Надія Миколаївна; Долгополова, Олена Вікторівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
Our experiment included 72 genograms of women aged 27-34, who participated in the practical course aimed at work with generic scenarios. We analyzed women`s genograms and identified transgenerational models of marriage.Transgenerational models of marriage can be reflected in each of 3-4 generations or have some influence through generation. It should be noted that transgenerational models of marriage have the following characteristics: the structure of marriage (family hierarchy, distribution of family roles), stages of family development (divorce, move, giving birth, remarriage), the level of satisfaction with the marriage.  We identified 4 transgenerational models of marriage that were frequently seen in the study sample. The 1st model “Patriarchal marriage” (14 genograms) is characterized by a significant role of a father and/or a grandfather, idealized and seen as a desired image of a man. The studied women with this family model showed some discontent with their husbands because they do not meet the expectations. The 2nd model “Matriarchal marriage” (14 genograms) is connected with strong female images (grandmother and/or great-grandmother), who were forced to take primary responsibility for the family because the man was a weak figure: he might have drunk, been sick, cheated, had problems with the law. Such relationships are very consistently reproduced in the families of female descendants.The 3rd model “Serial monogamy” (10 genograms) is characterized by the common features of two marriages from previous generations. Most often the 1st of them is described as unconscious and early, and the 2nd marriage as a more successful one. One of the options is that there are children in one marriage, and the other couple has problems with fertility. The 4th model “Misalliance” is an alliance of people with a consciously different social, educational and material status. The fact of the partners’ inconsistencies is emphasized and passed as a family mythology. This misalliance is reproduced in the generations of the descendants.Recommendations are offered for marital psychotherapy, taking into account the influence of the transgenerational model of marriage on the interactions of couples.